Face Attack Online: Unpacking Conflicts in Multimodal Group Chats - Fan Cao; Vanessa Ruiling Yu (Journalism and Media)
This study focuses on analyzing face attacks in the conflict discourse of cross-linguistic online chats on the instant message application WeChat among a group of international students at a prestigious university in China. Drawing on the previous impoliteness theory of Leech and Culpeper, this article selectively combines these two theories and proposes that in face-attack studies, especially with respect to online discourses, impolite multimodal discourse should be considered and subsumed in the theoretical framework. It is found that a wide array of face attacks in conflict discourse manifest themselves both in verbal discourse as well as in multimodal counterparts. The present study might shed light on online impoliteness research that is beyond monolingual and single-mode contexts.